Experimental Study on the Flow and Heat Transfer Characteristics of TiO(2)-Water Nanofluids in a Spirally Fluted Tube - Qi, Cong (Nanoscale Res Lett, 2017)
The flow and heat transfer characteristics of TiO(2)-water nanofluids with different nanoparticle mass fractions in a spirally fluted tube and a smooth tube are experimentally investigated at different Reynolds numbers. The effects of pH values and doses of dispersant agent on the stability of TiO(2)-water nanofluids are discussed. The effects of nanoparticle mass fractions and Reynolds numbers on Nusselt numbers and frictional resistance coefficients in the spirally fluted tube and the smooth tube are also investigated. It is found that TiO(2)-water nanofluids in the spirally fluted tube have a larger enhancement than that in the smooth tube. The heat transfer enhancement and the increase in frictional resistance coefficients of TiO(2)-water nanofluids in the spirally fluted tube and the smooth tube for laminar flow and turbulent flow are compared. It is found that there are a larger increase in heat transfer and a smaller increase in frictional resistance coefficients for turbulent flow than that for laminar flow of TiO(2)-water nanofluids in the spirally fluted tube. The comprehensive evaluations for the thermo-hydraulic performance of TiO(2)-water nanofluids in the smooth tube and spirally fluted tube are also discussed.